A New Literature Review on Financialization - Qi, Hanying (Journal of Accounting, Business and Finance Research, 2019)
Financialization is a phenomenon that concerned the increasing development of finance sector and has received much attention since the 20th century. Especially after the financial crisis in 2008, the financial development has entered a new stage, and the finance sector has become a dominant and important industrial sector in most of economies. The academic community has conducted extensive discussions on it and the researches on financialization involve a wide range theme. Therefore, this paper mainly reviews the typical literature which focused on financialization since 2008. It mainly covers six aspects, including the definition and characteristics of financialization, the motivation and realization mechanism of financialization, and four pairs of relationships including the relationship of financialization and financial crisis, financialization and economic growth, financial and industrial development, financialization and financial supervision. This literature extends a more comprehensive understanding of the development and impact of financialization and shows us the research fields that we could do more research on.